Physical Justification of an Increase in the Efficacy of Radiofrequency Systems for Myocardial Ablation; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Evtushenko A. V.; Evtushenko V. V.; Bykov A. N.; Sergeev V. S.; Syryamkin V. I. Vladimir Ivanovich; Kistenev Y. V.; Anfinogenova Ya. J. Yana Jonovna (Mechanical Engineering Technology, 2016)
Title screen